Multi-Omics Analysis of the Expression and Prognosis for FKBP Gene Family in Renal Cancer - Sun, Zeqiang; Qin, Xin; Fang, Juanjuan; Tang, Yueqing; Fan, Yidong (Frontiers in Oncology, 2021)
Background The FK506-binding protein (FKBP) is a family of intracellular receptors that can bind specifically to the immunosuppressant FK506 and rapamycin. Although FKBPs play crucial roles in biological processes and carcinogenesis, their prognostic value and molecular mechanism in clear cell renal cell carcinoma (ccRCC) remain unclear. Methods Using pan-cancer data from The Cancer Genome Atlas (TCGA) and public databases, we analyzed the expression and correlation of FKBPs in 33 tumor types. Survival and Cox regression analyses were employed to explore the prognostic value of FKBPs. The relationship with tumor microenvironment and stemness indices was taken into account to evaluate the function of FKBPs. We constructed a risk score model to predict the prognosis of patients with ccRCC. The receiver operating characteristic (ROC) curve was performed to further test the prognostic ability of our model. Nomogram, joint effects analysis, and clinical relevance were performed to assist the clinician. Gene set enrichment analysis (GSEA) and cell line experiments were performed to investigate the function and molecular mechanisms of FKBPs in patients with ccRCC. Paired clinical specimens and multi-omics analysis were used to further validate and explore the factors affecting gene expression in ccRCC patients. Results The expression levels of FKBP10 and FKBP11 were higher in ccRCC tissues than in normal tissues. The alteration in expression may be because of the degree of DNA methylation. Increased expression levels of FKBP10 and FKBP11 were associated with worse overall survival (OS). More importantly, GSEA revealed that FKBP10 is mainly involved in cell metabolism and autophagy, whereas FKBP11 is mainly associated with immune-related biological processes and autophagy. Cell Counting Kit 8 (CCK-8) and Transwell assays revealed that knockdown of FKBP10 and FKBP11 inhibits proliferation, migration, and invasion of the ccRCC cell line. Conclusion FKBP10 and FKBP11 play important roles in ccRCC phenotypes and are potential prognostic markers as well as new therapeutic targets for patients with ccRCC.